2015
DOI: 10.1590/s1519-99402015000100021
|View full text |Cite
|
Sign up to set email alerts
|

Parâmetros fisiológicos e desempenho para ovelhas Santa Inês e cordeiros ½ Dorper - Santa Inês nas estações verão e inverno

Abstract: RESUMO SUMMARYThis study aimed to evaluate the physiological parameters and performance of sheep Santa Inês and Dorperlambs ½-SantaInes in summer and winter seasons. 160 Santa Inês sheep and 189 ½ Dorper lambs were used -Santa Inês completely randomized in two treatments, summer: 80 sheep and 92 lambs and winter: 80 sheep and 97 lambs.Was recorded environmental the environmental parameters of air temperature (Ta°C), relative humidity (% RH), wind speed (Vvms-1) and black globe temperature (Tg°C) and physiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In sheep, Eustáquio Filho et al (2011) observed that temperature of 25 °C and relative air humidity of 65% maximized production and productivity in Santa Inês breed, and animals kept at temperatures above the thermal comfort zone (TCZ) might have difficulty eliminating the excessive load, consequently increasing the rectal and skin temperature (ST) and the respiratory and cardiac rate (Queiroz et al, 2015;Titto et al, 2016;Furtado et al, 2017;Seixas, Melo, Tanure, Peripoli, & McManus, 2017). Thermal stress causes several changes in animal physiology, including a reduction in feed efficiency and intake and disturbances in water, protein, energy, and mineral balance, limiting animal production and reproduction (Marai, El-Darawany, Fadiel, & Abdel-Hafez, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In sheep, Eustáquio Filho et al (2011) observed that temperature of 25 °C and relative air humidity of 65% maximized production and productivity in Santa Inês breed, and animals kept at temperatures above the thermal comfort zone (TCZ) might have difficulty eliminating the excessive load, consequently increasing the rectal and skin temperature (ST) and the respiratory and cardiac rate (Queiroz et al, 2015;Titto et al, 2016;Furtado et al, 2017;Seixas, Melo, Tanure, Peripoli, & McManus, 2017). Thermal stress causes several changes in animal physiology, including a reduction in feed efficiency and intake and disturbances in water, protein, energy, and mineral balance, limiting animal production and reproduction (Marai, El-Darawany, Fadiel, & Abdel-Hafez, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In sheep , Eustáquio Filho et al (2011) observed that temperature of 25 °C and relative air humidity of 65% maximized production and productivity in Santa Inês breed, and animals kept at temperatures above the thermal comfort zone (TCZ) might have difficulty eliminating the excessive load, consequently increasing the rectal and skin temperature (ST) and the respiratory and cardiac rate (Queiroz et al, 2015;Titto et al, 2016;Furtado et al, 2017;Seixas, Melo, Tanure, Peripoli, & McManus, 2017). Thermal stress causes several changes in animal physiology, including a reduction in feed efficiency and intake and disturbances in water, protein, energy, and mineral balance, limiting animal production and reproduction (Marai, El-Darawany, Fadiel, & Abdel-Hafez, 2007).…”
Section: Introductionmentioning
confidence: 99%